Stabilization of copper dioxygen compounds: design, synthesis, and characterization - Börzel, Heidi; Comba, Peter (Chemistry - a European journal, 1999)
The design of a new type of binucleating ligand, which stabilizes end-on (μ-peroxo)dicopper(II) compounds (see picture) at ambient temperature, was achieved through molecular modeling.